050-IARTIFICIAL CHORDAE IN A VARIETY OF LEAFLET PROLAPSES: DIFFERENT APPROACHES USING THE FOLDING LEAFLET TECHNIQUE. (October 2014) - Fuster, R. Garcia; Paredes, F.; Mena, A.; Juez, M.; Gil, O.; Hornero, F.; Martínez-León, J.
Abstract : Objectives: Mitral valve neochordal repair may be a complex procedure in cases of large areas of prolapse. We describe the use of a novel technique in different anatomical situations. Methods: A new technique for extensive neochordal repair was used in 4 patients with different types of prolapse: posterior, anterior, commissural and bileaflet prolapse. The neochordae were attached to the corresponding papillary muscle with a single stitch and then were implanted on the leaflet weaving the artificial chordae along the surface of coaptation. Free-edge leaflet remodelling was achieved to obtain a wide surface of coaptation. Neochordal length was determined after folding the prolapsing leaflet towards the annulus. The annular plane was considered as the main reference to adjust the height of the artificial chordae. Results: Neochordal repair was successfully performed in all these types of prolapse. Implantation of multiple neochordae was necessary. This procedure was capable of creating a large surface of coaptation in cases of complex commissural repair or large areas of prolapse on both leaflets, particularly in severe Barlow disease. Postoperative transoesophageal echocardiography (TEE) revealed adequate mitral leaflet coaptation, trivial residual mitral regurgitation (MR) and absence of systolic anterior motion (SAM). Conclusion: This procedure might facilitate the use of extensive neochordal repair in complex cases of prolapse on both leaflets. A variety of affected areas was considered to evaluate this technique with excellent functional results.